2014
DOI: 10.1002/ajh.23714
|View full text |Cite
|
Sign up to set email alerts
|

A novel mutation in the SLC40A1 gene associated with reduced iron export in vitro

Abstract: Ferroportin disease is an inherited disorder of iron metabolism and is caused by mutations in the ferroportin gene (SLC40A1). We present a patient with hyperferritinemia, iron overload in the liver with reticuloendothelial distribution and also in the spleen, and under treatment with erythropheresis. A molecular study of the genes involved in iron metabolism (HFE, HJV, HAMP, TFR2, SLC40A1) was undertaken. In vitro functional studies of the novel mutation found in the SLC40A1 gene was performed. The patient was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 37 publications
(42 reference statements)
0
12
0
Order By: Relevance
“…Mutations N144H/T/D, Y64N/H, L240E, C326Y/S/F, S338R, Y501C, D504N and H507R have been found in patients with FPN1 ‐associated haemochromatosis, but functional analysis is rarely reported. In vitro functional studies of the p.L129P mutation on ferroportin showed it impairs its capacity to export iron from cells but does not alter its sensitivity to hepcidin . Recently, a novel mutation p.R178Q was identified in 22 patients from six independent families in Europe, and in vitro studies showed that mutant reduced the ability of FPN1 to export iron without causing protein mislocalization .…”
Section: Discussionmentioning
confidence: 99%
“…Mutations N144H/T/D, Y64N/H, L240E, C326Y/S/F, S338R, Y501C, D504N and H507R have been found in patients with FPN1 ‐associated haemochromatosis, but functional analysis is rarely reported. In vitro functional studies of the p.L129P mutation on ferroportin showed it impairs its capacity to export iron from cells but does not alter its sensitivity to hepcidin . Recently, a novel mutation p.R178Q was identified in 22 patients from six independent families in Europe, and in vitro studies showed that mutant reduced the ability of FPN1 to export iron without causing protein mislocalization .…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in OTOF , which functionally triggers membrane fusion and exocytosis, may provide a link between calcium signaling and cancer [ 22 , 32 , 33 ]. SLC40A1 is a cell membrane protein that has been identified to mediate cellular iron efflux [ 23 , 34 ] and contribute to the invasive phenotype [ 35 ]. Mutations in ISPD may cause Walker-Warburg syndrome [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…FPN is strongly regulated by iron status and is the only known ferrous iron exporter in mammals. FPN mutations in humans lead to iron-loading disorders (11). Ferrous iron is oxidized by hephaestin, a copper-containing membrane-bound ferroxidase that co-localizes with FPN in the basolateral membrane (12).…”
Section: Molecular Regulation Of Iron Absorptionmentioning
confidence: 99%